Assessing the Impact of Fixed Asset Intensity and Financial Performance on Tax Avoidance Using a Quantitative Model: Independent Commissioners as Moderators - Intan Rahma Sari; Muhammad Fikhram Ali Islami; Endri Purnomo (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effect of fixed asset intensity and financial performance on tax avoidance with independent commissioners as a moderating variable in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Methodology: The research employs a quantitative approach using panel data analysis with the Random Effect Model (REM). The dependent variable is tax avoidance measured by the Effective Tax Rate (ETR), while the independent variables consist of fixed asset intensity and financial performance measured by Return on Assets (ROA). The moderating variable is the proportion of independent commissioners. Results: The results show that (1) financial performance has a significant effect on tax avoidance, (2) fixed asset intensity has no significant effect on tax avoidance, (3) independent commissioners have no direct significant effect on tax avoidance, (4) independent commissioners moderate the relationship between financial performance and tax avoidance, and (5) independent commissioners also moderate the relationship between fixed asset intensity and tax avoidance. Simultaneously, all independent variables and their moderating interactions have a significant effect on tax avoidance. Findings: These findings support agency theory, indicating that the supervisory role of independent commissioners can influence management behavior in managing corporate tax obligations. Novelty & Originality: The novelty of this study lies in the examination of independent commissioners as a moderating variable in the relationship between financial performance and fixed asset intensity on tax avoidance, a moderating role that has been rarely explored in prior research. Its originality emerges from the use of panel data analysis in the consumer non-cyclicals sector during the post-pandemic period. Conclusions: This study provides empirical evidence for accounting and taxation literature and serves as a reference for companies and regulators to enhance governance and tax transparency in Indonesia. Type of Paper: This paper is an empirical research paper.